Model Socioenvipreneur Melalui Inisiasi Bank Sampah Berbasis Masyarakat - Mutoharoh Mutoharoh; Naila Najihah; Luluk Muhimatul Ifada; Zainal Alim Adiwijaya (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Suboptimal waste management in Bangunharjo Village has led to environmental degradation and a decline in community quality of life. In response to this condition, a community service program was implemented through mentoring activities and the initiation of a community-based waste bank adopting a socioenvipreneur approach. The program involved members of the Family Welfare Empowerment (PKK) group from 24 neighborhood units (RT) and was carried out using a Participatory Learning and Action method that emphasized active community engagement throughout all stages of the program. Program success indicators included the establishment of waste bank management structures at the neighborhood level with a minimum participation target of 50% of RTs, the completeness of administrative records and activity reports, and the achievement of sustainable operational margins. Implementation over a six-month period, from May to October, demonstrated that the application of direct financial incentive and sanction mechanisms was more effective in maintaining stable and consistent community participation than the waste donation model. The average waste sales revenue generated per neighborhood unit ranged from IDR 1,500,000 to IDR 2,000,000. The socioenvipreneur-based waste bank approach demonstrates its feasibility as a community empowerment strategy that integrates social, environmental, and economic dimensions.